Additive effect of Moringa oleifera leaf meal and pomegranate (Punica granatum) peel powder on productive performance, carcass attributes and histological morphology of ileum in Japanese quails - Saira Maqsood; Shabana Naz; Areesha Sikandar; Sajida Arooj; Abdulwahed Fahad Alrefaei; Muhammad Israr (Journal of Applied Animal Research, 2024)
The experiment aimed to evaluate the combined effects of supplementing Japanese quail diets with Moringa oleifera leaf meal (MOLM) and pomegranate peel powder (PPP) on growth, carcass quality and ileum histology. Four groups were formed: a control group, MOLM (0.2%), PPP (7.5%) and a combination of both (0.2% MOLM + 7.5% PPP). The control group exhibited the highest weight gain, followed by the MOLM group, with no significant differences in feed intake or conversion ratio. Carcass analysis showed significant differences in liver, heart and gizzard weights, with the mixed diet group having the highest values. However, wings and dressed weight percentages were unaffected by the treatments. Sensory evaluation revealed improved organoleptic properties in the mixed diet group. Histological examination demonstrated enhanced ileum morphology in the mixed diet group, with significant improvements in villi length and villus/crypt depth ratio. Overall, supplementation with 0.2% MOLM and 7.5% PPP positively impacted carcass quality, sensory attributes and bird health. These findings suggest the potential benefits of combining MOLM and PPP in quail diets to enhance growth and overall health, highlighting the importance of further research in poultry nutrition.